2012
DOI: 10.1091/mbc.e12-01-0077
|View full text |Cite
|
Sign up to set email alerts
|

Local control of phosphatidylinositol 4-phosphate signaling in the Golgi apparatus by Vps74 and Sac1 phosphoinositide phosphatase

Abstract: Signaling by phosphatidylinositol 4-kinases (PI4Ks) in the Golgi apparatus controls lipid homeostasis and protein-sorting pathways. Signaling is shown to be terminated on the medial cisterna by a complex of a PI4K effector, Vps74, and Sac1, the major PtdIns4P phosphatase in the cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
81
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(87 citation statements)
references
References 43 publications
6
81
0
Order By: Relevance
“…A Golgi PI(4)P effector, GOLPH3, is involved in Golgi-plasma membrane transport and in the glycosylation of proteins (8,34,35). In yeast, Vps74, the ortholog of human GOLPH3, binds directly to Sac1 (36). We found that expression of GOLPH3 wt, but not GOLPH3 R90L, resulted in an increase in PI(4)P levels in the Golgi apparatus.…”
Section: Discussionmentioning
confidence: 76%
“…A Golgi PI(4)P effector, GOLPH3, is involved in Golgi-plasma membrane transport and in the glycosylation of proteins (8,34,35). In yeast, Vps74, the ortholog of human GOLPH3, binds directly to Sac1 (36). We found that expression of GOLPH3 wt, but not GOLPH3 R90L, resulted in an increase in PI(4)P levels in the Golgi apparatus.…”
Section: Discussionmentioning
confidence: 76%
“…Sul2 (a sulfur permease), two plasma membrane-associated t-SNAREs (Sso1 and Sso2), and Rvs161, a lipid raft protein, were also isolated, consistent with the role of Rsp5 in membrane protein trafficking. Other membrane-associated interacting proteins included Vti1 and Sac1, which are Golgi membrane proteins, and Pil1, which is localized to the mitochondrial membrane [77][78][79].…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in negative charge of the cis-and medial-Golgi relative to the TGN and late Golgi is the result of two factors. First, the negatively charged PtdIns(4)P is concentrated in the later Golgi because of the constant cycling of the PtdIns(4)P phosphatase Sac1 between the cis-Golgi and ER (33,34). Second, phosphatidylserine, another major negatively charged phospholipid, is located mostly in the inner leaflet of the ER and cis-Golgi membranes but in the outer leaflet of compartment membranes later in the secretory pathway (35).…”
Section: Discussionmentioning
confidence: 99%